Heavy metal figurations: Music consumption, subcultural control and civilizing processes. (September 2015) - Sinclair, Gary; Dolan, Paddy
Drawing from Eliasian figurational theory and data obtained in Ireland during a 3-year participant observation of both the live and online spaces of the scene, we argue that control, both individual and social, plays a vital part in shaping heavy metal figurations. We focus on the role of the subcultural code in integrating participants into the scene, enabling the enactment of cathartic rituals, and its importance in signifying hierarchy and the distribution of subcultural capital. In particular, we place emphasis on bodily forms of control and emotional self-steering and we consider how the management of aggression in heavy metal subculture is indicative of wider civilizing processes. Such findings are considered within the context of previous consumer culture theory research that has called for studies that incorporate broader socio-historical perspectives.